An Assessment of Teenage Pregnancy in Zimbabwe. The Case of Manicaland and Mashonaland Central Provinces (London Journal of Medical and Health Research, 2025)
Young people are a window of hope and a demographic dividend in many developing countries, including Zimbabwe. As such, societies must be conducive to nurturing a new generation that will spearhead the fourth industrial revolution agenda in the country. However, young people are faced by a myriad of sexual and reproductive health (SRH) problems which include unintended pregnancies and the consequent unsafe abortions.This study aims to assess the prevalence of teenage pregnancies in Manicaland and Mashonaland Central Provinces, identify the factors contributing to teenage pregnancy in these regions, and examine their consequences. The study utilised a triangulation of qualitative and quantitative methods, including surveys, focus group discussions (FGDs), and key informant interviews (KIIs). A survey quantified the magnitude of teenage pregnancies facing young people in Zimbabwe The survey involved 600 female adolescents aged 10-19 years, with the number of participants from each province determined using a probability proportional to size approach. FGDs were undertaken so as to obtain data on community perceptions on teenage pregnancy as well as the socio-cultural and religious beliefs underlying teenage pregnancies in Zimbabwe. The KII provided service provider level information on the challenges faced by young people and key statistics on incidence of teenage pregnancies. They also provided factors underlying teenage pregnancies. Purposive sampling was employed for the selection of participants in the FGDs and KIIs. Quantitative data were analysed using the Statistical Package for Social Sciences (SPSS), while qualitative data were analysed using thematic analysis and NVIVO version 11.The study findings revealed that 16% of the adolescents aged 10-19 years had experienced pregnancy. Various factors were associated with teenage pregnancy, including age, ethnicity, marital status, self-efficacy, knowledge of pregnancy, attitudes towards pregnancy and condom use, orphan hood, religion, religiosity, peer pressure, poverty, socio-cultural practices, sexual abuse, social media, transactional sex and the Internet.Based on the study findings, it is recommended to enhance female adolescent empowerment through life skills initiatives
Keywords: epidemic; Cameroon; Cholera; Edea; young people; Zimbabwe; Assessment; Teenage pregnancy; Manicaland; Mashonaland Central